MEWUJUDKAN VISI MA TENTANG BADAN PERADILAN YANG AGUNG MELALUI UNDANG-UNDANG JABATAN HAKIM - Siti Nurjannah (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
Judges official status has been affirmed as a state official, but in fact on some aspect on it is still bound by the Civil Service system. Therefore judge positions are often said to be dual status as state officials and civil servants. Nullifying the dual status is, in fact has caused serious problems in terms of both managerial and related to the potential reduction of judicial independence. If the independence start to reduce, the implications of the problems of the post of Judge is hampering efforts to realize the vision of the Supreme Court which is to realize the Supreme Courts.Keywords : Supreme Court Vision, Acts, and Official state of Judges